The Effect Of Open Chain Exercises With And Without Resistance On Fatigue During Hemodialysis - Najan, Swarali Shivnath; Jagtap, Vaishali (Journal of Neonatal Surgery, 2025)
Background: The cases of chronic kidney diseases is increasing day with higher fatality. One of the commonly used treatment method for chronic kidney disease is hemodialysis. Prevalence of hemodialysis is increasing as the prevalence of chronic kidney disease is increasing. Patients who are receiving hemodialysis many times suffers from poor functional capacity , quality of life, reduced physical strength , altered mental status, fatigue. Intradialytic exercises helps in improving cardiovascular health, respiratory health, improve physical function and mental status. Method: Sample size was 50, derived using the standard formula. The inclusion criteria were, Subjects undergoing hemodialysis having fatigue Age group 18-60 years , person willing to participate. The exclusion criteria were Patients having psychological problems, Acute or chronic conditions like MI, Congestive heart failure, unstable during dialysis, risk of fracture because this condition may worsen the condition of patient Result: The total number of subject participated in this study was 50. The result of this study showed that in all age groups 18-29 years, 30-39 years, 40-49 years, 50-59 years there is significant improvement from pre- to post- interventions according to the Fatigue severity scale Conclusion: According to the data obtained grom the data assessment sheet and search results, The data indicates that open chain exercises with and without resistance significantly reduce fatigue severity across all age groups studied (18-29 years, 30-39 years, 40-49 years , and 50-60 years)